2018
DOI: 10.1002/bio.3442
|View full text |Cite
|
Sign up to set email alerts
|

Solvatochromic study of 3‐N‐(N′‐methylacetamidino)benzanthrone and its interaction with dopamine by the fluorescence quenching mechanism

Abstract: The change in photophysical properties of the organic molecule due to solvatochromic effect caused by different solvent environments at room temperature gives information about the dipole moments of 3-N-(N'-methylacetamidino)benzanthrone (3-MAB). The quantum yield, fluorescence lifetime of 3-MAB was measured in different solvents to calculate radiative and non-radiative rate constants. The results revealed that the excited state dipole moment (μ ) is relatively larger compared to the ground state dipole moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…These dyes are characterized by efficient fluorescence, large extinction coefficients, excellent colour characteristics, high thermostability and photostability; therefore, they have a very wide range of applications in optics, solar cells, for textiles, polymers, daylight fluorescent pigments, laser dyes, etc. . Our previous study demonstrated high lipid‐associating ability of a series of newly synthesized benzanthrone amino and amidino derivatives .…”
Section: Introductionmentioning
confidence: 87%
“…These dyes are characterized by efficient fluorescence, large extinction coefficients, excellent colour characteristics, high thermostability and photostability; therefore, they have a very wide range of applications in optics, solar cells, for textiles, polymers, daylight fluorescent pigments, laser dyes, etc. . Our previous study demonstrated high lipid‐associating ability of a series of newly synthesized benzanthrone amino and amidino derivatives .…”
Section: Introductionmentioning
confidence: 87%
“…[ 9 ] Solvatochromism is the ability of a chemical substance to reversibly change its absorbance or emission spectra colour due to a change in solvent polarity. [ 10 ] Halochromism is the ability of pH‐sensory substances to change colour at different pH. [ 11 ] Colorimetric and emission chemical detectors are distinguished by their high sensitivity and rapid detection.…”
Section: Introductionmentioning
confidence: 99%
“…Among the known fluorophore structures, the polarization of the chromophoric system of benzanthrone derivatives yields intense fluorescence emission combined with a bright colour [1,2] that, can vary widely. That determines their respective applications: in liquid-crystalline systems for electro-optical displays [3,4,5,6], as fluorescent solvatochromic probes for DNA intercalations [7], for membrane studies [8,9], as biomedical probes for proteins, lipids, and cells [10,11] or as sensors for aliphatic amines in an aqueous medium [12,13,14].…”
Section: Introductionmentioning
confidence: 99%